A DDS-Based Wait-Free Phase-Continuous Carrier Frequency Modulation Strategy for EMI Reduction in FPGA-Based Motor Drive - Chen, Yangyang; Yang, Ming; Long, Jiang; Xu, Dianguo; Blaabjerg, Frede (IEEE transactions on power electronics, 2019)
In ac motor drives, the fixed-frequency harmonic components of output voltage and current from the inverter with fixed-frequency pulsewidth modulation usually lead to electromagnetic interference (EMI). The spread spectrum clock generation (SSCG) is a widely used solution for this problem. Adjusting the switching frequency to reduce EMI is one kind of practicable scheme among SSCG methods. How to design an optimal or suitable modulation profile is a research emphasis of scholars and has been discussed in depth in many literatures. However, apart from the modulation profile, the mode and quality of carrier are also important and can be improved. In most frequency modulation methods, due to the limitation of the conventional carrier generation mode, the implementation of the new frequency instruction has to wait for the termination of the last switching period. In order to eliminate the waiting state and design a simpler algorithm, this paper has proposed a wait-free phase-continuous carrier frequency modulation (WPCFM) strategy by combining the direct digital frequency synthesizer theory and proper temporal planning of control interruptions. Besides, a theoretical analysis of WPCFM, including quantization error, frequency jitter, phase delay, and voltage distortion, has been finished. Moreover, compared with conventional methods, a more convenient, feasible, and simpler field-programmable gate array based algorithm implementation method and the control structure of WPCFM are also introduced. The analysis shows that, although WPCFM causes a slight increase of the current ripple, it can solve the partial frequency nonuniform distribution problem of the conventional method, and it has a potential value of applications in the wide band gap motor drive systems. The effectiveness of the WPCFM is verified by several sets of EMI reduction experiments where classical periodic carrier frequency modulations are applied.